Work Stress of Online Motorcycle Taxi Drivers: The Role of Coworker Support, Autonomy and Affective Occupational Commitment - Fenika Wulani; Tuty Lindawati; Y.B.Budi Iswanto (LPPM Universitas Terbuka, 2022)
Purpose – Online motorcycle taxi driving is a field of work that has recently become a work option for some people. However, it could be this choice because of the compulsion that can cause stress. Drawing on social cognitive theory, this study investigates the antecedents of online motorcycle taxi drivers work stress, by considering coworker support, autonomy, and affective occupational commitment. Methodology – Data collection was carried out by surveying questionnaires, with 89 online motorcycle taxi drivers in Surabaya as respondents. Data analysis was done using Partial Least Square-Structural Equation Modeling (PLS-SEM). Findings – Supportive of social cognitive theory, this study finds that coworker support and autonomy positively influence affective occupational commitment, while affective occupational commitment is likely to reduce work stress. Coworker support and autonomy have no significant direct effect on work stress. Affective occupational commitment mediates the relationship between coworker support and work stress. Originality – Previous studies on online motorcycle taxi drivers tend to identify organizational commitment and examine the effect of work stress on work attitudes. The present study considers affective occupational commitment as an antecedent of work stress, and a mediator of the influence of coworker support and autonomy, on online motorcycle taxi drivers' work stress in Surabaya.